2006
DOI: 10.1021/ma0613584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carboxy-Functionalized Multiwall Nanotubes (MWNT−COOH) on the Crystallization and Chain Conformations of Poly(ethylene terephthalate) PET in PET−MWNT Nanocomposites

Abstract: Multiwall nanotubes that have undergone acidic treatment of varying duration were melt-compounded with poly(ethylene terephthalate) (PET) in a batch-mixer in order to create nanocomposite structures. The samples were pressed into films and annealed above the crystallization temperature of the polymer. Fourier Transform infrared (FT-IR) as well as Raman spectroscopies were utilized to monitor the gauche to trans transformations due to the annealing process with respect to the duration of the treatment of nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 58 publications
(106 reference statements)
5
46
0
3
Order By: Relevance
“…A different study on PET-nanotube composites manufactured using melt extrusion and compression molding showed an increase in the crystalline fraction at the expense of the trans conformer in the amorphous phase. 236 The RAF was not quantified in this study however. Cebe et al also examined polytrimethylene terephthalate and showed that the RAF increased with nanotube addition which was almost exactly compensated by a decrease in the material participating in the glass transition, that is, the fractional crystallinity did not change.…”
Section: Semicrystalline Polymersmentioning
confidence: 86%
“…A different study on PET-nanotube composites manufactured using melt extrusion and compression molding showed an increase in the crystalline fraction at the expense of the trans conformer in the amorphous phase. 236 The RAF was not quantified in this study however. Cebe et al also examined polytrimethylene terephthalate and showed that the RAF increased with nanotube addition which was almost exactly compensated by a decrease in the material participating in the glass transition, that is, the fractional crystallinity did not change.…”
Section: Semicrystalline Polymersmentioning
confidence: 86%
“…In many polymer systems after introduction of carbon nanotubes the increase in crystallization temperature, enhancing in nucleation density and in some causes reduction of crystallization time was observed [35,43,[46][47][48][49][50]. The effect of the presence of COOH functionalized MWCNT in PTT matrix on the melting and crystallization processes was studied by DSC.…”
Section: Effect Of Mwcnts Addition On Thementioning
confidence: 99%
“…Thermal properties of PTT and PTT/MWCNTs nanocomposites T g -glass transition temperature; T m , "H m -temperature and enthalpy of melting respectively; "C p -change of heat capacity;T c, on -onset temperature of crystallization; T c , "H c -temperature and enthalpy of crystallization respectively; x c -degree of crystallinity of the sample; "T = T m -%T c -degree of supercooling [43,[48][49]. Correlation of spectroscopic measurements with DSC have shown that acid treated MWCNTs present in PET nanocomposites not only enhanced crystallinity but also lead to a much better polymer crystalline order [49]. The presence of MWCNTs in PET matrix transforms trans conformers of the noncrystalline phase into crystalline domains with the nanotubes acting as moderate nucleation agents.…”
Section: Effect Of Mwcnts Addition On Thementioning
confidence: 99%
“…Some authors treat such complex melting in PET as melting/recrystallization/remelting [18,45]. At a relatively high cooling rate for PET and its nanocomposites, the segment of the amorphous phase that would otherwise form an ordered amorphous phase seems to have vitrified.…”
Section: Dsc Analysis For Pristine Pet Nanodiamond and Graphene Pet mentioning
confidence: 99%